Effect of sodium dodecyl sulfate surfactant on methane hydrate formation: a molecular dynamics study - Choudhary, Nilesh; Hande, Vrushali R.; Roy, Sudip; Chakrabarty, Suman; Kumar, Rajnish (Journal of Physical Chemistry B, 2018)
In experimental studies, it has been observed that the presence of sodium dodecyl sulfate (SDS) significantly increases the kinetics of hydrate formation and the final water-to-hydrate conversion ratio. In this study, we intend to understand the molecular mechanism behind the effect of SDS on the formation of methane hydrate through molecular dynamics simulation. Hydrate formation conditions similar to that of laboratory experiments were chosen to study hydrate growth kinetics in 1 wt % SDS solution. We also investigate the effect of interactions with isolated SDS molecules on methane hydrate growth. It was observed that the hydrophobic tail part of the SDS molecule favorably interacts with the growing hydrate surface and may occupy the partial hydrate cages while the head groups remain exposed to water.